Developing small business in the coordinate system of socio-economic space of the national economy - Е. V. Romanenk (Вестник СибАДИ)
The problems of small business’ development as a systematic and integral formation are considered in the article. The place of small business in the socio-economic space of the national economy is determined. There drawn conclusions on transformative impact of small business’ subjects on the existing socio-economic system and its individual structural elements.